Analysis Of Population And Increase In Msmes On Economic Growth In Indonesia - Perdinan Petrus Manurung; Kiky Hardiansyah Siregar; Uswatun Hasanah (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the Number of Population and the Increase of MSMEs on Economic Growth in Indonesia. Where there are bound variables, namely GDP (Gross Domestic Product) and There are two independent variables, namely the Number of Population and the Number of MSMEs. This study uses secondary data by searching for data through the Central Statistics Agency (BPS) Website and the Indo Data Website. The data analysis model in this study uses Multiple Linear Regeresi. The results of the study showed that the variables of Population and Number of MSMEs had a significant effect on GDP (Gross Domestic Product).